Editorial - S. Hamilton, Gregory; Luz Lopez Rodriguez, Maria (Central Nervous System Agents in Medicinal Chemistry, 2012)
Recent years have seen a sea-change in the pharmaceutical industry and the way in which it seeks new medicines. The decline in productivity of the sector, as defined by the number of drugs successfully discovered and developed per R&D spend, has been declining for many years, as documented in numerous studies. (See for example, Scannell et al., Nature Reviews Drug Discovery, 2012, 11, 191 - 200, and references cited therein.) One result has been a somewhat precipitous reduction in the size of the R&D divisions of many large pharmas; many thousands of scientists and others have lost their livelihoods. Many companies have sent large swaths of their discovery work to overseas contract outfits, particularly in China and India. Pharmaceutical research in CNS agents has certainly been affected by these changes, with some organizations essentially getting out of the field entirely. The continued difficulty of seeking new medicines for complex central disorders such as Alzheimer's, Parkinson's, and schizophrenia, and the expense of clinical trials coupled with a high failure rate, has led inexorably to a downsizing of pharma CNS programs in an era of short-term focus on profitability by the larger companies.....